1998
DOI: 10.1007/s002449900301
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Level Biomarkers in Sentinel Slugs as Cost-Effective Tools to Assess Metal Pollution in Soils

Abstract: In previous laboratory experiments, slugs were shown to be sensitive to metal pollution. Therefore, they might be invaluable instruments for biological assessment of soil pollution. The present investigation was carried out to validate previous laboratory results in a field study. Slugs were collected from an abandoned copper mine (Parys mountain top, PMT), from a site 7 km away from the mine (Parys mountain bottom, PMB), and from a clean site (Snowdonia Cwm Idwal, SCI) in Wales in early July 1994. Whole soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 32 publications
2
21
0
2
Order By: Relevance
“…Analogous adaptations in the digestive epithelium thickness of mollusks have been previously reported as an effect of changes in environmental quality as increased bioavailability of pollutants (Lowe et al 1981;Vega et al 1989;Marigo´mez et al 1990Marigo´mez et al , 1991Marigo´mez et al , 1992Cajaraville et al 1992). Marigo´mez et al (1996Marigo´mez et al ( , 1997 also found a clear evidence of severe adaptative changes in the digestive gland of mollusks following long-term/ chronic exposure to pollutants. According to Morgan et al (2002), the earthworm chloragocyte suffers morphological alterations to cope with larger quantities of metals.…”
Section: Discussionmentioning
confidence: 89%
“…Analogous adaptations in the digestive epithelium thickness of mollusks have been previously reported as an effect of changes in environmental quality as increased bioavailability of pollutants (Lowe et al 1981;Vega et al 1989;Marigo´mez et al 1990Marigo´mez et al , 1991Marigo´mez et al , 1992Cajaraville et al 1992). Marigo´mez et al (1996Marigo´mez et al ( , 1997 also found a clear evidence of severe adaptative changes in the digestive gland of mollusks following long-term/ chronic exposure to pollutants. According to Morgan et al (2002), the earthworm chloragocyte suffers morphological alterations to cope with larger quantities of metals.…”
Section: Discussionmentioning
confidence: 89%
“…Such structural changes can be assessed morphometrically, a technique that is sufficiently sensitive to detect epithelial thinning due to environmental stress in the digestive epithelia and reproductive tissues of several invertebrates (Vega et al, 1989;Marigomez et al, 1998;Siekierska and Urbanska-Jasik, 2002). Morphological alterations are not uncommon among organisms exposed to extreme environments.…”
Section: Morphometry and Cell Compositionmentioning
confidence: 99%
“…Land snails such as Helix aspersa and Arianta arbustorum have previously been used for the estimation of urban (Regoli et al 2006;Itziou & Dimitrids 2009) or industrial (Marigomez et al 1998) pollution, due to their ability to accumulate trace metals in their tissues (Beeby & Richmond 2002;Viard et al 2004). …”
Section: Introductionmentioning
confidence: 99%